Screening of Antibacterial Activities of the Endophytic Fungi Isolated from the Leaves of Medinilla speciosa Blume - Puteri Amelia; Rachma Ayunda; Saiful Bahri (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Endophytes or endophytic fungi have been investigated as a store house of bioactive compound. This study was aimed to evaluate the potential antibacterial activity of endophytic fungi isolated from Medinilla speciosa Blume. The antibacterial test was determined by measuring the inhibition zone with disk-diffusion method. Twenty endophytes were isolated from the leaves of Medinilla speciosa Blume and identified morphologically. The results demonstrated that ten isolates showed variation in their antibacterial activity against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Bacillus subtilis ATCC 6633, and Shigella dysenteriae ATCC 13313. Further investigation will be needed to explore and identify the bioactive molecules of the isolated endophytic fungi.